Peningkatan kualiti diri melalui intervensi interpersonal (Improving Self Qualities Through Interpersonal Intervention) - Laila Wati Madlan; Chua, Bee Seok; Murnizam Halik; Ferlis Hj.Bahari; Jasmine Adela Mutang (2015)
The study aimed to identify whether social emotional intelligence training can increase the level of interpersonal. This quasi-experimental study used self evaluation report that was given during the pre and post tests after 14 weeks of training. Each training was 2 hours each week. Second year students of Psychology at Universiti Malaysia Sabah participated in this study. 19 students were selected into the expeimental group and received an intervention, while 22 students were selected for the control group. The selection of participants was based on students who had low scores for social emotional intelligence using the Emotional Quotient Inventory (EQ-i) that consists of 133 items, divided into 5 components and 15 subscales. Pre test was given at the starting of the semester to get the basic scores and comparisons for the outcome after the participants received training using the ‘Modul Latihan Kecerdasan Emosi Sosial’ which was developed by the researchers. Wilcoxon and Mann-Whitney analyses were used to examine the difference between pre and post social emotional intelligence training within and between groups. The results showed that social emotional intelligence interpersonal skills increased after training in the treatment group. The comparison between the control group and the treatment group showed that there was a significant difference. In conclusion, social emotional intelligence training (interpersonal) has a positive effect on participants in the treatment group.